Design and Development of a Low-Cost Educational Platform for Investigating Human-Centric Lighting (HCL) Settings - George K. Adam; Aris Tsangrassoulis (Computers)
The design of reliable and accurate indoor lighting control systems for LEDs’ (light-emitting diodes) color temperature and brightness, in an effort to affect human circadian rhythms, has been emerging in the last few years. However, this is quite challenging since parameters, such as the melanopic equivalent daylight illuminance (mEDI), have to be evaluated in real time, using illuminance values and the spectrum of incident light. In this work, to address these issues, a prototype platform has been built based on the low-cost and low-power Arduino UNO R4 Wi-Fi BLE (Bluetooth Low Energy) board, which facilitates experiments with a new control approach for LEDs’ correlated color temperature (CCT). Together with the aforementioned platform, the methodology for mEDI calculation using an 11-channel multi-spectral sensor is presented. With proper calibration of the sensor, the visible spectrum can be reconstructed with a resolution of 1 nm, making the estimation of mEDI more accurate.